Guest Encapsulation Scope of a Triptycene-Based Pd2L4 Coordination Cage - Hasegawa, Shota; Baksi, Ananya; Chen, Bin; Clever, Guido H. (Organic Materials, 2022)
The scope of a lantern-shaped, triptycene-based Pd2L4 coordination cage to encapsulate various carbon-rich guests was investigated. The cage was found to bind two molecules of corannulene and a variety of C60 derivatives in moderate to quantitative yields. Non-disruptive extraction of encapsulated fullerene derivative PC61BM from the cage was demonstrated by the simple addition of CS2 into an acetonitrile solution of the host–guest complex. This process can be accomplished in a layer-to-layer fashion, and thus, the recovered cage can be further utilized in a recycling process. As this self-assembled host is readily synthesized and able to transfer fullerenes and a range of its derivatives into polar organic solvents, it allows facilitating purification, chemical modification and solid-state processing of fullerenes for a range of materials applications.
Keywords: supramolecular chemistry; host–guest complexes; fullerenes